Status of the Building Blocks for Sustainable Water, Sanitation, and Hygiene (WASH) Systems in Nepal: A Review - Yadav, Maheshwar Prasad; Silwal, Kumar Prasad (Nepal Journal of Multidisciplinary Research, 2023)
The paper aims at reviewing the building blocks of sustainable water, sanitation, and hygiene (WASH) systems in the context of Nepal. The study consisted of a descriptive research design based on secondary data that were collected from different published documents. The review was made through descriptive comparison, percentages, graphs, and ratios to compare whether the country’s status is in line with the global context. The study concludes that the proportion of the population having safely managed water services in Nepal (16 percent) is quite lower than the global average (73 percent). Moreover, the proportion of the population having safely managed sanitation services in Nepal (51 percent) is slightly lower than the global average (57 percent). Similarly, the proportion of the population having basic hygiene services in Nepal (64 percent) is lower than the global average (75 percent). Furthermore, the findings on the status of water, sanitation, and hygiene (WASH) systems are mixed in the context of Nepal. Some of them have good progress and some of them need to be accelerated to go a long way to achieve sustainable development goals (SDGs) by 2030. The study further concludes that institutionalization, policy and legislation, and accountability mechanisms at the federal level have been initiated while it is yet to materialize at the provincial and local levels. In the case of planning, only 10 percent of rural/municipalities completed their WASH plan. In terms of finance, there is not only a resource gap but also two-thirds of the total country’s WASH budget has been allocated at the federal level. Action research should be prioritized to capture learning and awareness leading to adaptation and knowledge creation in the sector. The study can be extended by incorporating the citizens’ views on WASH systems strengthening in the context of Nepal.